Comparison Between LigaSure Haemorrhoidectomy and Conventional Haemorrhoidectomy - Kumar, Rohit; Shafiq, Mahrukh; Ali, Aun; Iqbal, Muhammad Mansoor; Shahid, Madeeha; Lakdawala, Yousaf (Biological and Clinical Sciences Research Journal, 2025)
Hemorrhoidectomy remains the gold standard for treating advanced (grade III and IV) hemorrhoids. LigaSure, a vessel-sealing technology, has emerged as an alternative to conventional excisional techniques, promising less operative trauma and improved recovery. However, comparative evidence in the local context remains limited. Objective: To evaluate the operational differences and recovery outcomes between LigaSure hemorrhoidectomy and conventional hemorrhoidectomy in patients with grade III and IV hemorrhoids. Methods: This prospective comparative study was conducted at Fazaia Ruth Pfau Medical College and P.N.S Shifa Hospital, Karachi, from August 1, 2023, to July 1, 2024. After approval from the institutional review board, 60 patients aged 18 to 75 years of both genders with symptomatic grade III or IV hemorrhoids requiring surgery were enrolled through non-probability consecutive sampling. Patients were allocated to undergo either LigaSure or conventional hemorrhoidectomy. Key variables assessed included operative time, intraoperative blood loss, postoperative pain (measured by Visual Analog Scale), complication rate, and length of hospital stay. Statistical analysis was performed using standard comparative methods with significance set at p < 0.05. Results: The mean operative time was significantly shorter in the LigaSure group (18 ± 4.6 minutes) compared to the conventional group (33.3 ± 6.5 minutes; p < 0.0001). Intraoperative blood loss was also significantly reduced in the LigaSure group (17 ± 6.3 mL vs. 34.3 ± 9.3 mL; p < 0.0001). Postoperative pain scores were lower in the LigaSure group (2 ± 1.16) than in the conventional group (6.17 ± 1.5; p < 0.0001). The incidence of postoperative complications was significantly lower in the LigaSure group (16%) compared to the conventional group (46%; p = 0.025). Conclusion: LigaSure hemorrhoidectomy offers a superior alternative to conventional techniques, demonstrating significantly reduced operative time, lower blood loss, less postoperative pain, and fewer complications. It presents a safe and effective surgical option for managing advanced hemorrhoids.